Evolution of coffee terms of trade of Costa Rica and Colombia - Rodríguez Lizano, Víctor (2017)
The evolution of terms of trade in agriculture has been widely discussed in the research agenda, nonetheless, there is no observable unique path in the agriculture sector. This research addresses the evolution of coffee´s terms of trade in traditional coffee growing Costa Rica and Columbia by comparing coffee export prices and crude oil import prices during a 10-year span. Terms of trade are estimated and analyzed. Fairtrade certification as well as private and national strategies to increase the value and differentiation of coffee in the international market are offered as possible reasons for differences in terms of trade for the two countries.